2020
DOI: 10.1039/d0sc01221a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed hydroalkylation of methylenecyclopropanes with simple hydrazones

Abstract: A palladium-catalyzed hydroalkylation of methylenecyclopropanes via selective C–C σ-bond scission was achieved, in which simple hydrazones served as carbanion equivalents. This method affords high yields of C-alkylated terminal alkenes with good functional group compatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 78 publications
1
12
0
1
Order By: Relevance
“…On the basis of the above results and previous studies ( 15 , 18 , 19 ), a plausible mechanism is proposed in Fig. 5D .…”
Section: Resultssupporting
confidence: 78%
“…On the basis of the above results and previous studies ( 15 , 18 , 19 ), a plausible mechanism is proposed in Fig. 5D .…”
Section: Resultssupporting
confidence: 78%
“…In addition, the Li group and others have demonstrated that other transition‐metal catalysts, including Ni, Pd, and Fe, [29] could efficiently be merged with the WK processes to realize different mechanistic pathways (Scheme 4). This results in a vastly expanded set of accessible coupling partners, such as alkyl halides, [30] dienes, [31] styrenes, [32] phenol derivatives, [33] and aryl halides [34] in Ni catalysis and methylenecyclopropanes, [35] alkynes, [36] allylic acetates, [37] and gem ‐difluorocyclopropanes [38] in Pd catalysis. Several plausible reaction pathways for the different catalytic systems were postulated, as shown in Scheme 4.…”
Section: Catalytic Methods For the Generation Of Alkyl Carbanions Fro...mentioning
confidence: 99%
“…Apart from alkynes, some highly strained cyclopropanes, such as methylenecyclopropanes [68] and gem ‐difluorocyclopropanes [69] also behaved as unsaturated electrophiles, which were amenable under the Pd‐catalyzed ring‐opening hydrobenzylation conditions.…”
Section: Deoxygenative Functionalizations Of Aldehydes and Ketonesmentioning
confidence: 99%